Optimization of a PCR Method for Detection of Lipase Gene in Bacillus subtilis: Detection of Lipase Gene - Mir Mohammad Sadeghi, Hamid; Yazdanian, Maryam; Moazen, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2006)
Lipases catalyze hydrolysis and synthesis of triacylglycerols. These enzymes, especially the microbial ones, have wide commercial and industrial usage. Bacillus subtilis lipase has interesting properties such as small size and tolerance to basic pH; therefore, developing techniques for its recognition and isolation is the focus of research in many laboratories. In the present study, two factors i.e. MgCl2 concentration and annealing temperature were manipulated for the optimization of the polymerase chain reaction (PCR) condition. As for the MgCl2 concentration, 2.5 mM produced the best results when the annealing temperature was kept at 55 oC. Regarding the annealing temperatures, the best amplification was obtained at 63.9 oC. It can be concluded that the PCR conditions for the detection of lipase gene in Bacillus subtilis has been optimized and can be used for the screening and isolation of these bacaterial strains.